EFEKTIVITAS MODEL HYBRID LEARNING PADA PEMBELAJARAN DI SEKOLAH WILAYAH DKI JAKARTA - Nadiah Nadiah; Kunaenih Kunaenih; Andhika Putra Muhammad (stit-islamic-village, 2023)
The COVID-19 outbreak that hit Indonesia had an impact on various existing sectors, including the education sector. The government is required to rack the brain in the implementation of learning. At SMK Negeri 50 Jakarta, hybrid learning has been implemented (25% of students in class and 75% at home using the Microsoft Teams application) to overcome this problem. and also the teacher who teaches. The purpose of this research is to find out how effectively the hybrid learning model is applied to help students understand, and whether the hybrid learning model can be continued for learning. The data was taken at SMKN 50 DKI Jakarta. Researchers conducted data analysis using a quantitative approach with this type of research using, Paired sample t-Test is a two-sample paired difference test. From the data obtained, it shows that the results of calculations with SPSS state that, a significance level of 5%, testing the effectiveness of the hybrid learning model shows that the average value of the test results after using the Hybrid Learning method has increased higher than before using the Hybrid Learning method or experiencing significant increase